DESIGN OF CAPACITIVE SENSING SYSTEM FOR HOLDUP MEASUREMENT IN TWO-PHASE STRATIFIED FLOW - LIM, LAM GHAI (2017)
Two-phase flow occurs in the presence of two immiscible components inside pipelines or process equipment. They are frequently found in the petroleum, nuclear and chemical industries. Different flow patterns can be observed when the two-phase components are flowing together, where stratified flow can be easily seen in gas-liquid and liquid-liquid flow at moderately low flow rate.